Chinese Investment, Social Relations, and Local Actors: The Case of IMIP in Central Sulawesi - Ridha Amaliyah (UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAWA TIMUR, 2025)
The expansion of Chinese foreign direct investment (FDI) in Indonesia, particularly in the nickel downstream sector, has reshaped local political and social dynamics in resource-rich regions. This article critically examines the relationship between Chinese companies and local actors through a case study of Indonesia Morowali Industrial Park (IMIP) in Central Sulawesi. Employing Alvin Camba’s concept of social embeddedness, the study analyzes how Chinese investment is sustained through interactions among firms, state elites, local governments, and civil society. Based on qualitative analysis of policy documents, media reports, and interviews, the findings reveal that IMIP’s operations are strongly embedded within Indonesia’s central government coalition elites, whose political support facilitates regulatory flexibility and minimizes local resistance. This elite alignment enables investment continuity but simultaneously weakens environmental governance and limits meaningful community participation. While IMIP contributes to local economic growth, it also generates social tensions related to labor practices, environmental degradation, and limited technology transfer. Corporate social responsibility and strategic communication are used to manage, rather than resolve, these structural issues. The article argues that Chinese investment in Indonesia is less driven by market efficiency alone than by political embeddedness within a strong regime. This dynamic highlights the asymmetric power relations between investors, the state, and local communities, raising critical questions about the long-term sustainability and social justice of resource-based development under the Belt and Road Initiative.